Strengthening Verbal Reasoning in Problem Solving Using TSD - Portilla Villamizar, Sonia Esmeralda (Uptc, 2024)
This article is focused on examining the results of the implementation of a pedagogical strategy in search of strengthening verbal reasoning in mathematical problem solving, based on Guy Brousseau's Theory of Didactic Situations, due to the difficulties that students of INEM Tunja have been presenting in verbal and mathematical competencies leading to low results in the different external tests presented. She used an action-participatory research with a population of 25 students. For the collection of information, a diagnostic test, field diaries, individual and collaborative work formats and information analysis were used.  The results showed that the strategy had a positive impact, since it allowed significant improvements in the processes of solving problem situations. In conclusion, the aforementioned theory is an effective means to strengthen verbal, mathematical and personal skills. It used an action-participatory research with a population of 25 students. For the collection of information, a diagnostic test, field diaries, individual and collaborative work formats and information analysis were used.  The results showed that the strategy had a positive impact, since it allowed significant improvements in the processes of solving problem situations. In conclusion, the aforementioned theory is an effective means to strengthen verbal, mathematical and personal skills.